Kekuasaan dan Kekuatan Bhuta dalam Teks Lontar Roga Sanghara Bhumi dan Covid-19 di Bali: Analisis Etnolinguistik - Ni Wayan Sumitri; I Wayan Arka (Ranah: Jurnal Kajian Bahasa, 2022)
This paper discusses the power of bhuta in the lontar (palm leaf) manuscript of Roga Sanghara Bhumi (RSB), in the context of Covid-19 in Bali, from an ethnolinguistic perspective. The RSB manuscript is a treasure documenting local knowledge reflecting Balinese Hindu culture about the existence of bhuta as a negative force causing disease outbreaks. The linguistic aspects examined and discussed include the integration of various lexico-grammatical elements, textually and contextually related to power and pandemics. The study is qualitative descriptive; important findings include the use of ethnolinguistic capital and local Balinese-Hindu symbols related to the conception/role of bhuta's power and rituals practiced by the Balinese, and how the Balinese maintain the dynamic balance of the universe's harmony and well-being. Evidence of ethnolinguistic resources includes multi-lingual diglossic features of Old Javanese-Sanskrit-Balinese and local Balinese-Hindu symbols, including the Balinese script and evil force repellent rituals such as caru offerings. RSB's striking textual feature is the persuasive narrative in the imperative mood. This is closely related to the function of RSB as a reference of advice to deal with pandemics. Cultural contextual features in RSB describe the cosmology, description and explanation of the occurrences of various outbreaks (sasab, gering, mrana, grubug) and the role of butha and its handling. Analysis in the context of Covid-19 is also provided. This paper underscores the importance of using local-traditional wisdom approaches in pandemic management to complement modern ones. AbstrakMakalah ini mengkaji power (kekuasaan/kekuatan) bhuta dalam teks lontar Roga Sanghara Bhumi (RSB), terkait Covid-19 di Bali, dari perspektif etnolinguistik. Teks RSB merefleksikan khazanah budaya Hindu-Bali terkait dengan keberadaan bhuta sebagai kekuatan negatif penyebab wabah penyakit. Aspek kebahasaan yang diperiksa dan dibahas mencakup integrasi berbagai elemen lexico-grammar kekuasaan/kekuatan, secara tekstual dan kontekstual terkait dengan pandemi. Kajiannya bersifat deskriptif kualitatif, menunjukkan temuan penting diantaranya penggunaan sumber daya etnolinguistik (ethno-linguistic capital) dan simbol-simbol lokal Bali-Hindu terkait konsepsi/peran power bhuta dan praktik-praktik ritual, serta dinamikanya untuk menjaga keseimbangan kerahayuan alam semesta. Bukti-bukti sumber daya etnolinguitik mencakup fitur diglosik multi/dwibahasa Jawakuna-Sanskerta-Bali dan simbol-simbol lokal Bali-Hindu termasuk aksara Bali dan ritual penolak kekuatan jahat seperti sesaji caru. Fitur tekstual RSB yang mencolok adalah naratif persuasif bermodus imperatif; ini terkait erat dengan fungsi RSB sebagai sumber petujuk/acuan untuk menghadapi pandemi. Fitur kontekstual kultural menggambarkan kosmologi, deskripsi dan penjelasan terjadinya berbagai wabah (sasab, gering, mrana, grubug) dan peran butha serta penanganannya. Analisisnya dalam konteks Covid-19 juga diberikan. Makalah ini menggarisbawahi pentingnya penggunaan pendekatan kearifan lokal-tradisional dalam penanganan pandemi untuk melengkapi pendekatan modern.